52-4+3x=x

Simple and best practice solution for 52-4+3x=x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 52-4+3x=x equation:



52-4+3x=x
We move all terms to the left:
52-4+3x-(x)=0
We add all the numbers together, and all the variables
2x+48=0
We move all terms containing x to the left, all other terms to the right
2x=-48
x=-48/2
x=-24

See similar equations:

| 9x-4-5x=x+4+x | | (2/3v-6)=(6-2/3v) | | x/8+x/7=8/9 | | -45-7x=-157 | | 90-4.75x=75-3.25 | | 4/b-39=2/b+1 | | 54-4=3x | | -2(-1.7x3.1)=4 | | 18x+12-8x=16 | | D-5=9d-2 | | 2x+7=2(x+9) | | -9(3+8a)=15 | | 25+4x=-35 | | n-8-(-2n+2)= | | 0.7x-2.5=1.1 | | 9*4*x=9x | | 2h-11=4 | | 3{x-2}+4=2 | | 0.06x-1.7=0.02x-1.3 | | 26=12+4.5r | | 49x-2=50x | | -7x+2(5x-17)=-7 | | 5-2x=3+x-4-3x  | | -8c+4=-3c+6 | | 16w-15w=10 | | x/2-15=-2 | | (6,-2)m=-3 | | 9t+5+3t-3= | | 4/3x-9=8-3/6x | | 105-2.5x=85-2x | | s+(-3)=-11 | | 8x+7=3x+5 |

Equations solver categories